Transition of Japanese commercial space: What has been lost from the commercial space? (Gremium, 2016)
This paper compares two types commercial spaces in modern Japan, which are shopping mall and “traditional” shopping district called “ShoTenGai”, fromthe viewpoint of commercial space as the third space in the city. Particularly, the ‘’shopping street’’ has been portrayed as nostalgia in the discourse about commercial spaces in Japan. Therefore, the transition of commercial space is always accompanied the description of the “Lost”. However, there is no unanimous opinion in what actually lost in the process of this transition. In this paper, we extract the category of commercial spaces by considering focus on discourse for both places. The research papers and journal articles that with different main argument and specific data are targeted for my analysis. After extracting the social category, through the comparison of the two discourses, I reveal the nature of “Lost” that take place in the commercial spaces as the third place in the city. I also discuss how this transition relates the changes in Japanese social relationship and community.